2021
DOI: 10.1155/2021/5523516
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Estrogen on Cardiovascular Disease Mediated by Oxidative Stress

Abstract: Perimenopause is an important stage of female senescence. Epidemiological investigation has shown that the incidence of cardiovascular disease in premenopausal women is lower than that in men, and the incidence of cardiovascular disease in postmenopausal women is significantly higher than that in men. This phenomenon reveals that estrogen has a definite protective effect on the cardiovascular system. In the cardiovascular system, oxidative stress is considered important in the pathogenesis of atherosclerosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 196 publications
(249 reference statements)
1
28
1
Order By: Relevance
“…In the case of the male population, the risk of cardiovascular disease increases linearly over time, and the atherosclerotic process develops continuously. On the other hand, due to the protective role of estrogen and its beneficial effects on the cardiovascular system, women of a fertile age may be protected from atherosclerosis [ 15 , 16 , 17 , 18 ]. This statement is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the male population, the risk of cardiovascular disease increases linearly over time, and the atherosclerotic process develops continuously. On the other hand, due to the protective role of estrogen and its beneficial effects on the cardiovascular system, women of a fertile age may be protected from atherosclerosis [ 15 , 16 , 17 , 18 ]. This statement is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the Austrian study appear to be different to that reported previously in younger individuals, where it was shown that men tend to have a higher rate of DNA damage than women [ 34 , 35 , 36 ], however, data in elderly people are rare. At younger age females usually show a better lifestyle and higher level of oestrogen, which provides them with a better defence system against free radical species [ 37 ]. This is diminished in elderly postmenopausal women and the advantage of women gradually disappears after menopause, which leads e.g., to a higher risk of cardiovascular disease in postmenopausal women than men of the same age, a trend that is largely attributed to the role of female oestrogen [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female mitochondria tolerate better both oxygen deprivation and oxidative damage than male mitochondria, 4 and women seem to be better protected from ischemia/reperfusion induced apoptosis. 4,42 Accordingly, estrogens can protect against oxidative stress 43,44 and modulate apoptosis. 45 Also physiological levels of testosterone in men are protective against such injury.…”
Section: Mechanistic Effects Of Sex Hormones On Cardiovascular Cellsmentioning
confidence: 99%